2020
DOI: 10.1111/jphp.13322
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, characterization, antidiabetic and antioxidative evaluation of a novel Zn(II)-gallic acid complex with multi-facet activity

Abstract: Objectives This study was done to synthesize a novel Zn(II)‐gallic acid complex with improved antidiabetic and antioxidative properties. Methods The complex was synthesized and characterized using Fourier Transform Infrared (FT‐IR) and 1H NMR. Cytotoxicity was evaluated using Chang liver cells and L6 myotubes. Radical scavenging and Fe3+‐reducing, as well as α‐glucosidase, α‐amylase and glycation inhibitory properties were measured. Glucose uptake was measured in L6 myotubes, while the complex was docked again… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 41 publications
0
17
0
Order By: Relevance
“…Phenolic acids, due to their hydrogen‐donating capacity and ability to form stable phenoxy radicals (Motloung et al., 2020), quench prooxidant radicals that can cause oxidative damage to biological molecules and mediate complications in several diseases, including diabetes (Chukwuma & Islam, 2017). Studies have shown that position of non‐carboxylic –OH group in phenolic acids can influence their radical scavenging activity, with those having –OH group at “ortho” and/or “ para ” position (eg, p‐hydroxybenzoic acid and derivatives) showing stronger radical quenching activity (Velika & Kron, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Phenolic acids, due to their hydrogen‐donating capacity and ability to form stable phenoxy radicals (Motloung et al., 2020), quench prooxidant radicals that can cause oxidative damage to biological molecules and mediate complications in several diseases, including diabetes (Chukwuma & Islam, 2017). Studies have shown that position of non‐carboxylic –OH group in phenolic acids can influence their radical scavenging activity, with those having –OH group at “ortho” and/or “ para ” position (eg, p‐hydroxybenzoic acid and derivatives) showing stronger radical quenching activity (Velika & Kron, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The DPPH (2,2‐diphenyl‐1‐picrylhydrazyl) and ABTS [2,2′‐Azino‐bis(3‐ethylbenzothiazoline‐6‐sulfonic acid) diammonium salt] radical scavenging assay, as well as the Fe 3+ reducing assay where used as in vitro models to measure the antioxidant properties of the test samples according to the protocols reported by Motloung et al. (2020).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…dextran). 105–107 In 2017, Yang and co-workers utilised Leuconostoc glucansucrase for the transglycosylation of gallic acid. 108 The resulting GA glycoside 23 (Fig.…”
Section: Anti-ageing Ingredientsmentioning
confidence: 99%
“…In a previous study (Motloung et al., 2020), Zn(II) was chemically combined with gallic acid in a 1:2 mole ratio, respectively, to form a Zn(II)‐gallic acid complex. It was shown that Zn(II) complexed with gallic acid through a Zn(O 4 ) coordination mode, which afforded the resulting complex two moieties of gallic acid, and thus, improved the innate antioxidant and bioactive property of the phenolic acid ligand by several folds, while conferring its insulin mimetic potentials on the complex (Figure 1).…”
Section: Figurementioning
confidence: 99%